Achieving work hardening by forming boundaries on the nanoscale in a Ti-based metallic glass matrix composite. (1st August 2020) - Fan, Jing; Rao, Wei; Qiao, Junwei; Liaw, P.K.; Şopu, Daniel; Kiener, Daniel; Eckert, Jürgen; Kang, Guozheng; Wu, Yucheng
Graphical abstract: Highlights: Ti41 Zr32 Ni6 Ta7 Be14 MGMC shows distinct tensile ductility with significant work-hardening capability. The generation of nano-boundaries at interface is the key factor to achieve the excellent mechanism properties. Finite element modeling was established to assist the interpretation of the deformation mechanism. The constitutive relationship of work-hardening exponent between the dendrites and the matrix were developed. Abstract: Achieving work hardening in metallic glass matrix composites (MGMCs) is the key to the extensive use of these attractive materials in structural and functional applications. In this study, we investigated the formation of nanoscale boundaries resulted from the interaction between matrix and dendrites, which favors the work-hardening deformation in an in-situ Ti41 Zr32 Ni6 Ta7 Be14 MGMC with β-Ti dendrites in a glassy matrix at room temperature. The microstructures of samples after tension were observed by high-resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD). The work-hardening mechanism of the present composites involves: (1) appearance of dense dislocation walls (DDWs), (2) proliferation of shear bands, (3) formation of boundaries on the nanoscale, and (4) interactions between hard and soft phases. A theoretical model combined with experimental data reveals the deformation mechanisms in the present work, proving that the in-situ dendrites with outstanding hardening ability in the glass matrix can provide the homogeneous deformation under tensile loading at room temperature.